Exploring the Capabilities of NeRF in Generating 3D Models - Fang, Shun (EAI Endorsed Transactions on AI and Robotics, 2024)
This review paper presents a comprehensive analysis of three cutting-edge techniques in 3D content synthesis: EG3D, DreamFusion, and Magic3D. EG3D, leveraging geometry-aware representations and generative adversarial networks, enables the generation of high-quality 3D shapes. DreamFusion integrates text-to-image diffusion models with neural rendering, opening new horizons for creative expression. Magic3D, on the other hand, extends text-to-image synthesis principles to 3D content creation, synthesizing realistic and detailed models. We delve into the theoretical frameworks, neural network architectures, and loss functions of these techniques, analyzing their experimental results and discussing their strengths, weaknesses, and potential applications. This review serves as a valuable resource for researchers and practitioners, offering insights into the latest advancements and pointing towards future directions for exploration in 3D content synthesis.
Keywords: NeRF; GANs; MLP; EG3D; DreamFusion; Magic3D